Internal anatomy of female striped mealybug, Ferrisia virgata Cockerell - Harshitha Prakash; Pawan Shukla; A. Ramesha; Himanshu Dubey; Gangavarapu Subrahmanyam; S. Manthira Moorthy (International Journal of Tropical Insect Science, 2026)

An IoT-enabled heart disease prediction framework using hybrid and multi-dilated convolution aided adaptive residual attention network - A. Moorthy; V. Sarala; C. Sivasankar; S. Parthiban; U. Samson Ebenezar (Physical and Engineering Sciences in Medicine, 2026)

Design and development of La0.5Sr1.5MnO4 coated defect rich TiOx as an efficient electrocatalyst for direct production of methane (CH4) via electrochemical H2O/CO2 co splitting - M. Praveen Kumar; Sasikumar Moorthy; A. Arulraj; Francisco V. Herrera Diaz; Suhail Mubarak; P. Sivakumar; Manavalan Rajesh Kumar; G. Murugadoss; Huiqing Fan; R.V. Mangalaraja (Fuel, 2025)

Phenome, repeatome, and transcriptome analysis to comprehend the structural and functional aspects of polyploid Morus serrata Roxb - Raju Mondal; Himanshu Dubey; A. Ramesha; Kunjupillai Vijayan; V. Nishitha Naik; S. Manthira Moorthy (Trees, 2025)

Construction of copper-cobalt bimetallic nanoparticles in the confined space of mesoporous silica KIT-6 support for the catalytic removal of organic contaminants - Krishnamoorthy Shanmugaraj; Santiago Bedoya; Daniela Gonzalez-Vera; Cristian H. Campos; Moorthy Mathivanan; Padmanaban Annamalai; A. Shanmugavani; Pazhanivel Thangavelu (Journal of Water Process Engineering, 2025)

Towards a liana plant functional type for vegetation models - Hans Verbeeck; Hannes P.T. De Deurwaerder; Elizabeth Kearsley; Sruthi M.Krishna Moorthy; Francis Mumbanza Mundondo; Kasper Coppieters; Stefan A. Schnitzer; Marcos Longo; Marc Peaucelle; Marijn Bauters; Félicien Meunier (Ecological Modelling, 2024)

Contrasting gut bacteriomes unveiled between wild Antheraea assamensis Helfer (Lepidoptera: Saturniidae) and domesticated Bombyx mori L. (Lepidoptera: Bombycidae) silkworms - Gangavarapu Subrahmanyam; Yeruva Thirupathaiah; N. Vijay; Rajal Debnath; K. P. Arunkumar; Mallikarjuna Gadwala; Prashant A. Sangannavar; S. Manthira Moorthy; Mahananda Chutia (Molecular Biology Reports, 2024)

Characterisation of indigenous entomopathogenic nematode, Steinernema abbasi PN-1 Elawad and its biocontrol potential against major lepidopteran pests - Nisha Mehra; Renu Pandey; P. Vireesha; A. V. Moorthy; Satya Kumar (International Journal of Tropical Insect Science, 2024)

Development of productive multi-viral disease-tolerant bivoltine silkworm breeds of Bombyx mori (Lepidoptera: Bombycidae) - L. Satish; L. Kusuma; A. V. Mary Josepha Shery; S. M. Moorthy; G. R. Manjunatha; V. Sivaprasad (Applied Entomology and Zoology, 2023)

Liana optical traits increase tropical forest albedo and reduce ecosystem productivity - Félicien Meunier; Marco D. Visser; Alexey Shiklomanov; Michael C. Dietze; J. Antonio Guzmán Q.; G. Arturo Sanchez‐Azofeifa; Hannes P. T. De Deurwaerder; Sruthi M. Krishna Moorthy; Stefan A. Schnitzer; David C. Marvin; Marcos Longo; Chang Liu; et al. (Global Change Biology, 2022)
Lianas are a key growth form in tropical forests. Their lack of self‐supporting tissues and their vertical position on top of the canopy make them strong competitors of resources. A few pioneer studies have shown that liana optical traits differ on average from those of colocated trees. Those trait discrepancies were hypothesized to be responsible for the competitive advantage of lianas over trees. Yet, in the absence of reliable modelling tools, it is impossible to unravel their impact on the forest energy balance, light competition, and on the liana success in Neotropical forests. To bridge this gap, we performed a meta‐analysis of the literature to gather all published liana leaf optical spectra, as well as all canopy spectra measured over different levels of liana infestation. We then used a Bayesian data assimilation framework applied to two radiative transfer models (RTMs) covering the leaf and canopy scales to derive tropical tree and liana trait distributions, which finally informed a full dynamic vegetation model. According to the RTMs inversion, lianas grew thinner, more horizontal leaves with lower pigment concentrations. Those traits made the lianas very efficient at light interception and significantly modified the forest energy balance and its carbon cycle. While forest albedo increased by 14% in the shortwave, light availability was reduced in the understorey (−30% of the PAR radiation) and soil temperature decreased by 0.5°C. Those liana‐specific traits were also responsible for a significant reduction of tree (−19%) and ecosystem (−7%) gross primary productivity (GPP) while lianas benefited from them (their GPP increased by +27%). This study provides a novel mechanistic explanation to the increase in liana abundance, new evidence of the impact of lianas on forest functioning, and paves the way for the evaluation of the large‐scale impacts of lianas on forest biogeochemical cycles.

Structure based virtual screening of natural product molecules as glycosidase inhibitors - N. S. Hari Narayana Moorthy; Natércia F. Brás; Maria J. Ramos; Pedro A. Fernandes (In Silico Pharmacology, 2021)

Modeling the impact of liana infestation on the demography and carbon cycle of tropical forests - Manfredo di Porcia e Brugnera; Félicien Meunier; Marcos Longo; Sruthi M. Krishna Moorthy; Hannes De Deurwaerder; Stefan A. Schnitzer; Damien Bonal; Boris Faybishenko; Hans Verbeeck (Global Change Biology, 2019)
There is mounting empirical evidence that lianas affect the carbon cycle of tropical forests. However, no single vegetation model takes into account this growth form, although such efforts could greatly improve the predictions of carbon dynamics in tropical forests. In this study, we incorporated a novel mechanistic representation of lianas in a dynamic global vegetation model (the Ecosystem Demography Model). We developed a liana‐specific plant functional type and mechanisms representing liana–tree interactions (such as light competition, liana‐specific allometries, and attachment to host trees) and parameterized them according to a comprehensive literature meta‐analysis. We tested the model for an old‐growth forest (Paracou, French Guiana) and a secondary forest (Gigante Peninsula, Panama). The resulting model simulations captured many features of the two forests characterized by different levels of liana infestation as revealed by a systematic comparison of the model outputs with empirical data, including local census data from forest inventories, eddy flux tower data, and terrestrial laser scanner‐derived forest vertical structure. The inclusion of lianas in the simulations reduced the secondary forest net productivity by up to 0.46 t C ha −1 year −1 , which corresponds to a limited relative reduction of 2.6% in comparison with a reference simulation without lianas. However, this resulted in significantly reduced accumulated above‐ground biomass after 70 years of regrowth by up to 20 t C /ha (19% of the reference simulation). Ultimately, the simulated negative impact of lianas on the total biomass was almost completely cancelled out when the forest reached an old‐growth successional stage. Our findings suggest that lianas negatively influence the forest potential carbon sink strength, especially for young, disturbed, liana‐rich sites. In light of the critical role that lianas play in the profound changes currently experienced by tropical forests, this new model provides a robust numerical tool to forecast the impact of lianas on tropical forest carbon sinks.

Binding mode of conformations and structure-based pharmacophore development for farnesyltransferase inhibitors - N. S. Hari Narayana Moorthy; Sergio F. Sousa; Maria J. Ramos; Pedro A. Fernandes (Medicinal Chemistry Research, 2016)

Design, synthesis and biological evaluation of novel arylidine-malononitrile derivatives as non-carboxylic inhibitors of protein tyrosine phosphatase 1B - Girdhar Singh Deora; Chandrabose Karthikeyan; N. S. Hari Narayana Moorthy; Vandana Rathore; Arun K. Rawat; Akhilesh K. Tamrakar; A. K. Srivastava; Piyush Trivedi (Medicinal Chemistry Research, 2013)

QSAR and pharmacophore analysis of thiosemicarbazone derivatives as ribonucleotide reductase inhibitors - N. S. Hari Narayana Moorthy; Nuno M. F. S. A. Cerqueira; Maria J. Ramos; Pedro A. Fernandes (Medicinal Chemistry Research, 2012)

QSAR analysis of 2-benzoxazolyl hydrazone derivatives for anticancer activity and its possible target prediction - N. S. Hari Narayana Moorthy; Nuno S. Cerqueira; Maria J. Ramos; Pedro A. Fernandes (Medicinal Chemistry Research, 2012)

Characteristics of spectral aerosol optical depths over India during ICARB - S. Naseema Beegum; K. Krishna Moorthy; Vijayakumar S. Nair; S. Suresh Babu; S. K. Satheesh; V. Vinoj; R. Ramakrishna Reddy; K. Rama Gopal; K. V. S. Badarinath; K. Niranjan; Santosh Kumar Pandey; M. Behera; et al. (Journal of Earth System Science, 2008)

Chemical characteristics of PM10 aerosols and airmass trajectories over Bay of Bengal and Arabian Sea during ICARB - L. A. K. Reddy; U. C. Kulshrestha; J. Satyanarayana; Monika J. Kulshrestha; K. Krishna Moorthy (Journal of Earth System Science, 2008)